Efektivitas Intervensi Mindfulness Untuk Menurunkan Tingkat Stress Pada Perawat Di RSUD Labuang Baji Kota Makassar - Nurul, Nadila; Suharni A. Fachrin; Andi Nurlinda (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Stress is an uncontrolled psychological and emotional response arising from interaction with the physical and non-physical environment. Work stress is considered a process of interaction between individuals and the work environment that represents the accumulation of negative emotions arising from work. These adverse reactions result in high-stress experiences over a fairly long period of time, which ultimately affects the physical and mental health of nurses. This study aimed to determine the level of stress in nurses, the level of stress in nurses before and after mindfulness intervention, and the effect of mindfulness intervention on stress levels in nurses. This study used a quasi-experimental mindfulness approach design and the Wilcoxon Rank Sum test to analyze research data. This study was conducted from May 22 - June 27 in 2024, with preparation and implementation. The population used as subjects were nurses aged 35-39 years who had a work period of >10 years, with a total of 20 people who met the criteria. The research results show the influence of mindfulness intervention on reducing stress levels in nurses at Labuang Baji Regional Hospital. Nurses must be able to become figures needed by their patients, sympathize with patients, always maintain their attention and focus, and be warm to patients. This method is effective in overcoming stress in spiritual awareness.